PENGARUH KEPEMIMPINAN PEDAGOGI TERHADAP PRESTASI BELAJAR SISWA DI SDN 057 BENGKULU UTARA - Eti Kurniawati; Adi Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pedagogical leadership is a fundamental and determinant aspect of basic education, focusing on accelerating the quality of learning and improving student achievement. This type of leadership relies not only on bureaucratic-administrative managerial competencies in school management, but also prioritizes a strategic vision for creating an effective, innovative, applicable, and fully student-centered teaching climate. This research article aims to analyze and examine in depth the influence of the application of pedagogical leadership on student achievement at SDN 057 North Bengkulu. By applying a descriptive, critical qualitative approach through an in-depth literature review and a review of the school's empirical documents, the analysis strongly indicates that effective pedagogical leadership acts as a primary catalyst in building a conducive academic environment, boosting teacher professionalism and instructional competence in the classroom, and stimulating active student engagement in meaningful learning schemes. The study concluded that there is a significant and linear relationship between strengthening pedagogical leadership implemented by principals and senior teachers and student achievement, ultimately contributing significantly to aggregate educational outcomes.